Les politiques d’appui à l’agriculture familiale au Brésil et au Maroc : quelques éléments de comparaison - Nicolas Faysse; Philippe Bonnal; Eric Sabourin (Confins)
The agricultural sector of Brazil and Morocco is characterized by extremes differences in terms of the size of the farms and their levels of equipment, of capital and of production techniques, The article compares the policies set up to support family farms in these two countries. In Brazil, policies have been specifically set up to support family farms for the past 20 years, with in particular the set-up of a specific ministry and specific policies. These policies include a plan to set up agrarian reform and to support agrarian reform projects, a support to credit access and integrated approaches for the development of marginalized rural areas. In Morocco, the main current policy is the Green Morocco Plan, which is based on two pillars: one dedicated to intensive production and the other one to areas with low agricultural potential. Public policies in both countries acknowledge the duality of the agricultural sector, but this duality is defined per area in Morocco, whereas is it based on explicit characteristics of farms in Brazil. In both countries, the core component of policies aiming to support family farms focuses on facilitating agricultural investment. However, in Morocco, policies aim to organize the integration of family farms within value chains. Moreover, since 2003, Brazilian policies involve more pluri-dimensional approaches that aim to develop the territories where family farms and native communities are more present.